D-statistical convergence of order ? and d-statistical boundedness of order ? in metric spaces - Kayan, Emine; Çolak, Rifat; Altin, Yavuz (Politechnica University of Bucharest, 2018)
In the present paper, we introduce and study d-statistical convergence of order ? d-statistical boundedness of order ? and d-strong p-Cesàro summability of order ? for sequences in a metric space. Furthermore, we investigate the relations between the sets of sequences which are d-statistically convergent of order ?, between the sets of sequences which are d-statistically bounded of order ? and between the sets of sequences which are d-strongly p-Cesàro summable of order ? for various values of ?’s in (0,1]. © 2018, Politechnica University of Bucharest. All rights reserved.
Keywords: Statistical boundedness of order ?; Statistical convergence; Statistical convergence of order ?; Strong p ? Cesàro summability of order ?; ?-density